A new species of the genus Chinoperla (Plecoptera: Perlidae) from southern China - Lü, Dongbiao; Yan, Yanhua; Li, Weihai; Wang, Hongliang (Zootaxa, 2019)
A new species of the perlid genus Chinoperla Zwick, C. biprojecta sp. nov. from Hainan Province of southern China is described. The male of the new species is easily distinguished from other known species by the pair of finger-like projections at posterior margin of the median sclerite of tergum 9.